Meta-Analysis Study: Environmental Risk Factors of Tuberculosis (TB) - Ratih Zahratul Jannah; R. Azizah; Juliana Binti Jalaludin; Lilis Sulistyorini; Kusuma Scorpia Lestari (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis and is a major cause of global health problems. Therefore, this study aims to analyze the risk factors of the physical environment in terms of ventilation, home density, and lighting, as well as to test their sensitivity to TB. Methods: The Meta-Analysis method was used with the PICOS technique, and a total of 11 articles were obtained through Google Scholar and Science Direct. Results and Discussions: The meta-analysis showed that home density posed the highest risk among the physical environment variables with a pooled PR = e1.33 = 3.781 (95% CI 1.10 – 1.56). Furthermore, the results were relatively on the variable of ownership and home density, and unstable on the lighting. Conclusion: Based on the results, home density had the highest risk among the physical environment variable. Therefore, the community is advised to improve promotive services by providing information related to TB, such as healthy homes and fulfilling requirements.